PENERAPAN REHABILITASI MEDIS DAN REHABILITASI SOSIAL TERHADAP PELAKU TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA JENIS GANJA (STUDI TERHADAP PUTUSAN PENGADILAN NEGERI CIBINONG NOMOR 167/PID.SUS/2018/PN.CBI.) - Reyner Darell Sidharta; R. Rahaditya (Fakultas Hukum Universitas Tarumanagara, 2022)
Indonesia as a constitutional state based on Pancasila and the 1945 Constitution containsregulations governing the order of people's lives which aim to create security and order in sociallife. In order to overcome the high level of narcotics abuse in Indonesia, the government issuedLaw Number 35 of 2009 concerning Narcotics and Circular Letter of the Supreme Court Number 4of 2010 concerning the placement of victims of abuse and narcotics addicts into medicalrehabilitation and social rehabilitation institutions for reference in sentencing. Furthermore, theresearch used is normative legal research, descriptive analytical research, secondary data types.Imprisonment is not an appropriate final means of punishment for victims of narcotics abuse, butvictims of narcotics abuse do not trade narcotics but for their own consumption, in contrast toperpetrators who become narcotics dealers or dealers who trade narcotics among the public.Article 127 paragraph (3) of the Law of the Republic of Indonesia Number 35 of 2009 concerningNarcotics states that